207k views
4 votes
Simplify the following expression (((b²+b-1)/(2b-1)-1) - (4-(8/(b+1))).

User Tarnisha
by
5.4k points

1 Answer

7 votes

Answer:


(b^(3) -10b^(2) +9b-4)/((2b-1)(b+1))

Explanation:

We have to simplify the following expression:

((( b²+b-1 )/( 2b-1 )-1 ) - ( 4-( 8/( b+1 )))

=
((b^(2)+b-1 )/(2b-1) -1)-(4-(8)/(b+1) )

=
((b^(2)+b-1-2b+1 )/(2b-1)) -((4b+4-8)/(b+1)){ By simplification of the terms}

=
(b^(2)-3b )/(2b-1) -(4b-4)/(b+1) {We have to add those two terms}

=
((b^(2)-3b)(b+1)-(4b-4)(2b-1) )/((2b-1)(b+1)) { The L.C.M. is ( 2b-1 )( b+1 ) }

=
(b^(3)-3b^(2)+b^(2)-3b-8b^(2) +4b+8b-4   )/((2b-1)(b+1))

=
(b^(3) -10b^(2) +9b-4)/((2b-1)(b+1)) ( Answer )

User Mazlum Tosun
by
5.1k points